Implementasi Aplikasi UKBM berorientasi STEM untuk meningkatkan hasil belajar fisika siswa - I Kadek Darsika Aryanta (Indonesian Journal of Educational Development, 2020)
This class action research aims to improve student physics learning outcomes and describe student responses to the application of STEM-oriented Independent Learning Unit applications. The subjects of this study were students of class XI MIPA 1 SMA Negeri Mandara. The object of this study is learning outcomes and student responses. This research was conducted in two learning cycles, with the stages in each cycle are planning, action, observation/evaluation, and reflection. Learning outcomes in question are abilities that include aspects of knowledge and skills collected by giving student worksheets (worksheets), assignments (homework), quizzes, and tests understanding the concept of the end of the cycle. Student response data were collected using a questionnaire. This research is said to be successful if the average student learning outcomes are 75 with classical completeness of 85%, and student responses are at least positive. The collected data is then analyzed descriptively. The analysis showed 1) the average value of student learning outcomes in the first cycle was 73 with classical completeness of 39% and in the second cycle was 80 with classical completeness of 100%; 2) student responses to the application of module in physics learning is with an average score of 84.64 and are in the positive category. Penelitian tindakan kelas ini bertujuan meningkatkan hasil belajar fisika siswa dan mendeskripsikan tanggapan siswa terhadap penerapan aplikasi Unit Kegiatan Belajar Mandiri berorientasi STEM . Subjek penelitian ini adalah siswa kelas XI MIPA 1 SMA Negeri Bali Mandara tahun pelajaran 2018/2019. Objek penelitian ini adalah hasil belajar, dan tanggapan siswa. Penelitian ini dilakukan dalam dua siklus pembelajaran, dengan tahapan-tahapan dalam tiap siklus adalah perencanaan, tindakan, observasi/evaluasi, dan refleksi. Hasil belajar yang dimaksud adalah kemampuan yang mencakup aspek pengetahuan dan keterampilan yang dikumpulkan dengan pemberian lembar kerja siswa (LKS), tugas-tugas (PR), kuis, dan tes pemahaman konsep akhir siklus. Data tanggapan siswa dikumpulkan dengan menggunakan kuisioner. Penelitian ini dikatakan berhasil jika rata-rata hasil belajar siswa 75 dengan ketuntasan klasikal 85%, dan tanggapan siswa minimal berkategori positif. Data yang telah terkumpul tersebut, selanjutnya dianalisis secara deskriptif. Hasil analisis menunjukkan 1) nilai rata-rata hasil belajar siswa pada siklus I sebesar 73 dengan ketuntasan klasikal 39% dan pada siklus II sebesar 80 dengan ketuntasan klasikal 100%; 2) tanggapan siswa terhadap penerapan aplikasi ukbm dalam pembelajaran fisika adalah dengan skor rata-rata sebesar 84,64 dan berada pada kategori positif.